2009
DOI: 10.1074/jbc.m807328200
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses the Induction of Indoleamine 2,3-Dioxygenase by Blocking the Janus-activated Kinase-Protein Kinase Cδ-STAT1 Signaling Pathway in Interferon-γ-stimulated Murine Dendritic Cells

Abstract: Indoleamine 2,3-dioxygenase (IDO) catalyzes the initial and rate-limiting step in the degradation of tryptophan and is strongly induced in interferon-␥ (IFN␥)-stimulated dendritic cells (DCs). IDO has recently been established as a key enzyme inT-cell suppression-mediated immune tolerance to tumors. STAT1 phosphorylation appears to play an important role in the control of IDO expression by IFN␥, but the precise regulatory mechanism remains obscure. Here we present a novel mechanism of IFN␥-induced IDO expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 48 publications
2
91
0
1
Order By: Relevance
“…As shown in this article, DC IDO expression and induction by LPS/IFN-g may also occur in a RelBindependent fashion. In support of a signaling pathway independent of the alternate NF-kB pathway, IDO is induced through STAT1 and IRF1 signaling downstream of the IFN-g receptor in DCs (60,61 Our conclusions that IFN-g and IDO are critical components of effective therapeutic immunoregulation of autoimmune disease are strongly supported by the literature in strains of mice prone to spontaneous Th1/Th17-mediated autoimmune disease. Although T EM and Treg IFN-g was induced in the current studies, regulatory IFN-g could also derive from NK or NKT cells to similar regulatory effect.…”
Section: Discussionsupporting
confidence: 74%
“…As shown in this article, DC IDO expression and induction by LPS/IFN-g may also occur in a RelBindependent fashion. In support of a signaling pathway independent of the alternate NF-kB pathway, IDO is induced through STAT1 and IRF1 signaling downstream of the IFN-g receptor in DCs (60,61 Our conclusions that IFN-g and IDO are critical components of effective therapeutic immunoregulation of autoimmune disease are strongly supported by the literature in strains of mice prone to spontaneous Th1/Th17-mediated autoimmune disease. Although T EM and Treg IFN-g was induced in the current studies, regulatory IFN-g could also derive from NK or NKT cells to similar regulatory effect.…”
Section: Discussionsupporting
confidence: 74%
“…IL-6 are not direct targets of miR181a and previous studies reported that IL-6 expression are regulated by MAPK, NF-jB, and STAT1 pathways [35][36][37][38][39]. Based on this knowledge, we used MAPK, NF-jB, and STAT1 pathway inhibitors to determine whether upregulation of IL-6 via miR-181a was dependent on these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism to suppress T cells used by DCs remains poorly understood, some work has shown that murine and human IDO-expressing DCs in TDLNs are able to degrade tryptophan and create profound T-cell anergy (41,42). Interestingly, curcumin also inhibits IDO significantly in IFN-g-stimulated murine bone marrow-derived DCs in vitro, resulting in reversing IDO-mediated suppression of T-cell function (43). Therefore, the effect of curcumin on IDO-expressing DCs of the host may be another mechanism contributing to enhanced efficacy of adoptive therapy and is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%